2016
DOI: 10.1002/0471141755.ph0506s72
|View full text |Cite
|
Sign up to set email alerts
|

Models of Inflammation: Carrageenan Air Pouch

Abstract: The subcutaneous air pouch is an in vivo model that can be used to study the components of acute and chronic inflammation, the resolution of the inflammatory response, the oxidative stress response, and potential therapeutic targets for treating inflammation. Injection of irritants into an air pouch in rats or mice induces an inflammatory response that can be quantified by the volume of exudate produced, the infiltration of cells, and the release of inflammatory mediators. The model presented in this unit has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
2
21
0
4
Order By: Relevance
“…In our experimental conditions the intraplantar injection of 1% carrageenan solution developed a biphasic response: an early inflammatory reaction and neurogenic pain, lasting for 6 h, and a second late phase (inflammator y hyperalgesia), with a peak intensity at 72 h and which progressively diminished after approximately 96 h [33,34]. The positive control drug IND determined a significant reduction in local inflammator y process after intraperitoneal administration, its effects being concordant with the reported literature data regarding the effects of this non-steroidal anti-inflammator y drug in this experimental model in rodents [12,13,35,36].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In our experimental conditions the intraplantar injection of 1% carrageenan solution developed a biphasic response: an early inflammatory reaction and neurogenic pain, lasting for 6 h, and a second late phase (inflammator y hyperalgesia), with a peak intensity at 72 h and which progressively diminished after approximately 96 h [33,34]. The positive control drug IND determined a significant reduction in local inflammator y process after intraperitoneal administration, its effects being concordant with the reported literature data regarding the effects of this non-steroidal anti-inflammator y drug in this experimental model in rodents [12,13,35,36].…”
Section: Resultssupporting
confidence: 83%
“…The degree of local inflammatory edema and its duration was assessed by using a plethysmograph (PanLab Apparatus). We measured the posterior paw volume according to the following scheme: before the induction of edema (initial volume at moment zero), at 24 h and 3 days after the inflammation was developed [13,14]. The results were expressed as percentage of reduction in inflammation, compared to initial volume in control animals.…”
Section: Experimental Part Materials and Methodsmentioning
confidence: 99%
“…Whether this is also the case in vivo remains to be elucidated. The observation that injected carrageenan causes inflammation [ 28 , 29 ] could even be explored as a potential adjuvant. Studies analyzing the attachment mechanisms of HPVs have shown that on epithelial cells, HPVs use heparan sulfate proteoglycans (HSPGs) as primary attachment factors [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the complex effectively released constituents capable of interfering in the production of chemical mediators, such as vasoactive amines and prostaglandins, responsible for vasodilation and the formation of inflammatory exudates [ 76 ]. A recent study by Martins et al (2017) showed that the systemic administration of same C. rhamnifolioides essential oil at doses of 25, 50, 100, and 200 mg/kg resulted in a significant reduction of carrageenan and dextran-induced edema [ 29 ].…”
Section: Discussionmentioning
confidence: 99%